Coating modified layered oxide positive electrode material, preparation method thereof and lithium ion battery
By using Al-doped Ba3NaRu2O9 and MgO composite materials to coat layered oxide positive electrode materials, the problem of insufficient cycling performance and stability of existing materials in lithium-ion batteries is solved, and higher battery performance and better Low capacity attenuation.
Patent Information
- Application Number
- CN202411989676.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The circulation performance and stability of the existing ternary layered oxide positive electrode materials in lithium-ion batteries still have room for improvement, especially after long-term use, the capacity attenuation is more obvious.
The coating-modified layer was prepared by mixing with the hydroxide precursor of the layered oxide positive electrode material and heat treatment, stirring and sintering. Oxide positive electrode material.
Through the coating modification technology, the stability and cycling performance of the positive electrode material are significantly improved, the capacity attenuation of the battery is reduced, and the overall performance of the battery is improved.
Smart Images

Figure CN119400843A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to the coating modification of a precursor of a positive electrode material for a lithium ion battery. Background Art
[0002] With the growing global demand for clean energy and efficient energy storage technology, lithium-ion batteries, as one of the most competitive energy storage devices, have become the focus of scientific research and industry. Positive electrode materials are one of the core components of lithium-ion batteries and greatly affect the electrical properties of lithium-ion batteries. Ternary layered oxide positive electrode materials have high energy density and long cycle life and are widely used in lithium-ion batteries. Even so, researchers are still actively exploring the surface modification technology of ternary layered oxide positive electrode materials to further improve their comprehensive performance. For example, CN118693261A discloses a layered positive electrode material, including a core and a first coating layer and a second coating layer that sequentially coat the core; the core includes a ternary material or a quaternary material doped with an anion X; the first coating layer includes a metal oxide Y, and the second coating layer includes a lithium salt Z. In-depth research on coating materials and coating processes has always been the focus of this field. Summary of the invention
[0003] The purpose of the present invention is to provide a coated modified layered oxide positive electrode material and a preparation method and application thereof.
[0004] To achieve the above objectives, the present invention provides the following specific technical solutions.
[0005] First, the present invention provides a coated modified layered oxide positive electrode material, comprising a core and a coating layer, wherein the chemical expression of the core is LiNi x Co y Mn z O 2 , wherein 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z=1; the material of the coating layer is Al-doped Ba 3 NaRu 2 O 9 and MgO composites.
[0006] In a further preferred embodiment, the mass of the material of the coating layer is 0.5-2% of the mass of the core.
[0007] In a further preferred embodiment, the Al-doped Ba 3 NaRu 2 O 9 The molar ratio of O to MgO is 1:4~4:1.
[0008] Secondly, the present invention provides a method for preparing a coated modified layered oxide positive electrode material, comprising: Al-doped Ba 3 NaRu 2 O 9 and uniformly mixed with a hydroxide precursor of a layered oxide cathode material, and then heat treated at 200-300° C. to obtain a precursor I; Precursor I was dispersed in ethanol solution, and then MgCl 2 6H 2 O, stirring to obtain a mixed slurry; Adding an ammonia solution to the mixed slurry and stirring until the pH value reaches 10-12, stop adding the ammonia solution; continue stirring for a period of time and then let it stand to obtain a precursor II; After being washed and dried, the precursor II is mixed with a lithium salt and sintered in an oxygen atmosphere to obtain a coated and modified layered oxide positive electrode material.
[0009] In a further preferred embodiment, Al-doped Ba is prepared by the following method: 3 NaRu 2 O 9 : Dissolve soluble salts of barium, sodium, ruthenium and aluminum in deionized water at a molar ratio of Ba, Na, Ru and Al of 3:1:2-a:a to obtain a mixed salt solution; wherein 0.05≤a≤0.2; The complexing agent solution is added to the mixed salt solution, and the water in the mixed salt solution is evaporated by heating and stirring; the evaporated material is further dried and calcined to obtain Al-doped Ba 3 NaRu 2 O 9 .
[0010] Preferably, the soluble salts of barium, sodium, ruthenium and aluminum are carbonates and / or nitrates, more preferably nitrates.
[0011] Preferably, the complexing agent is one of citric acid, polyethylene glycol and urea, more preferably citric acid.
[0012] Preferably, the ratio of the molar amount of the complexing agent to the total molar amount of Ba, Na, Ru and Al in the mixed salt solution is 1-1.4:1.
[0013] Preferably, the water in the mixed salt solution is evaporated at 90-150° C. by means of an oil bath.
[0014] Preferably, the drying temperature is 100-180°C.
[0015] Preferably, the calcination temperature is 700-1000° C., and the calcination time is 12-20 hours.
[0016] The heat treatment time is 3 to 6 hours.
[0017] In a further preferred embodiment, Al-doped Ba 3 NaRu 2 O 9 , hydroxide precursors of layered oxide cathode materials, MgCl 2 6H 2 The molar ratio of O is 0.5~2:100:0.5~2.
[0018] In a further preferred embodiment, the chemical expression of the hydroxide precursor of the layered oxide positive electrode material is Ni x Co y Mn z (OH) 2 , where 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z=1.
[0019] In a further preferred embodiment, the ratio of the total molar amount of Ni, Co, and Mn in the precursor II to the molar amount of Li in the lithium salt is 1:1.01~1.1.
[0020] In a further preferred embodiment, the sintering temperature is 700-1000° C. and the sintering time is 12-20 hours.
[0021] Based on the same inventive concept, the present invention provides a lithium-ion battery, comprising the aforementioned coated and modified layered oxide positive electrode material.
[0022] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects: The material of the coating layer is Al-doped Ba 3 NaRu 2 O 9 The composite material of MgO can improve the stability of the positive electrode material, reduce the capacity decay of the battery, and further improve the cycle performance of the battery.
[0023] The preparation method is relatively simple, easy to operate, and has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the SEM image of the hydroxide precursor of nickel, cobalt and manganese in Example 1.
[0025] Figure 2 This is the SEM image of precursor I in Example 1.
[0026] Figure 3 This is the SEM image of the coated and modified positive electrode material obtained in Example 1.
[0027] Figure 4 This is the cycle performance curve of the battery. DETAILED DESCRIPTION
[0028] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0029] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0031] Example 1 (1) Preparation of Al-doped Ba 3 NaRu 2 O 9 Barium nitrate, sodium nitrate, ruthenium nitrate and aluminum nitrate were dissolved in deionized water at a molar ratio of Ba, Na, Ru and Al of 3:1:1.9:0.1; then citric acid in an amount 1.2 times the total molar amount of Ba, Na, Ru and Al was added and stirred to obtain a mixed solution.
[0032] The mixed solution was heated in an oil bath at 120°C, stirred, and evaporated to dryness. The evaporated material was dried at 180°C for 5 h, then transferred to a muffle furnace and calcined at 900°C for 15 h to obtain Al-doped Ba 3 NaRu 2 O 9 .
[0033] (2) Preparation of precursor materials A nitrate solution of nickel, cobalt and manganese was prepared according to a molar ratio of Ni:Co:Mn of 0.9:0.05:0.05. A hydroxide precursor of nickel, cobalt and manganese was prepared by a coprecipitation process.
[0034] (3) Coating modification Al-doped Ba 3 NaRu 2 O 9The hydroxide precursors of nickel, cobalt and manganese were mixed evenly in a molar ratio of 1:100, and then heat treated at 250 °C for 4 h. After cooling, precursor I was obtained.
[0035] Precursor I was added to the ethanol solution, dispersed, and then 1% MgCl 2 6H 2 O, stirring (it may also be further ultrasonicated after stirring) to obtain a mixed slurry.
[0036] A 2.0 mol / L ammonia solution was added to the mixed slurry at a rate of 2 mL / min until the pH value of the mixed solution reached 11. The addition of ammonia solution was stopped, and the mixture was mechanically stirred for 1 h and then allowed to stand for 2 h to obtain precursor II.
[0037] Precursor II was mixed with lithium carbonate in a ratio of the total molar amount of Ni, Co, and Mn to the molar amount of Li of 1:1.05, and then sintered at 850°C in an oxygen atmosphere for 16 h to obtain a coated modified positive electrode material.
[0038] Figure 1 This is the SEM image of the hydroxide precursor of nickel, cobalt and manganese.
[0039] Figure 2 This is the SEM image of precursor I.
[0040] Figure 3 This is the SEM image of the coated modified positive electrode material.
[0041] Comparative Example 1 The nickel-cobalt-manganese hydroxide precursor is directly mixed with lithium carbonate in a ratio of the total molar amount of Ni, Co, and Mn to the molar amount of Li of 1:1.05, and then sintered at 850° C. in an oxygen atmosphere for 16 hours to obtain a positive electrode material.
[0042] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that there is no Al-doped Ba in the coating material. 3 NaRu 2 O 9 Specifically: Add the nickel-cobalt-manganese hydroxide precursor to the ethanol solution, disperse it, and then add 1% MgCl 2 6H 2 O, stirring (it may also be further ultrasonicated after stirring) to obtain a mixed slurry.
[0043] A 2.0 mol / L ammonia solution was added to the mixed slurry at a rate of 2 mL / min until the pH value of the mixed solution reached 11, and then the addition of ammonia solution was stopped. The mixture was mechanically stirred for 1 hour and then allowed to stand for 2 hours to obtain precursor II.
[0044] Precursor II was mixed with lithium carbonate in a ratio of the total molar amount of Ni, Co, and Mn to the molar amount of Li of 1:1.05, and then sintered at 850°C in an oxygen atmosphere for 16 h to obtain a coated modified positive electrode material.
[0045] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that there is no MgO in the coating material. Specifically: Al-doped Ba 3 NaRu 2 O 9 The hydroxide precursors of nickel, cobalt and manganese were mixed evenly in a molar ratio of 1:100, and then heat treated at 250°C for 4 hours. After cooling, the precursor I was obtained.
[0046] Precursor I was mixed with lithium carbonate in a ratio of the total molar amount of Ni, Co, and Mn to the molar amount of Li of 1:1.05, and then sintered at 850° C. in an oxygen atmosphere for 16 hours to obtain a coated modified positive electrode material.
[0047] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that Ba 3 NaRu 2 O 9 Aluminum doping is performed. Specifically: (1) Preparation of Ba 3 NaRu 2 O 9 Barium nitrate, sodium nitrate and ruthenium nitrate were dissolved in deionized water at a molar ratio of Ba, Na and Ru of 3:1:2; then citric acid in an amount 1.2 times the total molar amount of Ba, Na and Ru was added and stirred to obtain a mixed solution.
[0048] The mixture was heated in an oil bath at 120 °C, stirred, and evaporated to dryness. The evaporated material was dried at 180 °C for 5 h, then transferred to a muffle furnace and calcined at 900 °C for 15 h to obtain Ba 3 NaRu 2 O 9 .
[0049] (2) Preparation of precursor materials A nitrate solution of nickel, cobalt and manganese was prepared according to a molar ratio of Ni:Co:Mn of 0.9:0.05:0.05. A hydroxide precursor of nickel, cobalt and manganese was prepared by a coprecipitation process.
[0050] (3) Coating modification Will Ba 3 NaRu 2 O 9 The hydroxide precursors of nickel, cobalt and manganese were mixed evenly in a molar ratio of 1:100, and then heat treated at 250°C for 4 hours. After cooling, the precursor I was obtained.
[0051] Precursor I was added to the ethanol solution, dispersed, and then 1% of the molar amount of the nickel-cobalt-manganese hydroxide precursor MgCl 2 6H 2 O, stirring (it may also be further ultrasonicated after stirring) to obtain a mixed slurry.
[0052] A 2.0 mol / L ammonia solution was added to the mixed slurry at a rate of 2 mL / min until the pH value of the mixed solution reached 11, and then the addition of ammonia solution was stopped. The mixture was mechanically stirred for 1 hour and then allowed to stand for 2 hours to obtain precursor II.
[0053] Precursor II was mixed with lithium carbonate in a ratio of the total molar amount of Ni, Co, and Mn to the molar amount of Li of 1:1.05, and then sintered at 850° C. in an oxygen atmosphere for 16 hours to obtain a coated modified positive electrode material.
[0054] Example 2 (1) Preparation of Al-doped Ba 3 NaRu 2 O 9 Barium nitrate, sodium nitrate, ruthenium nitrate and aluminum nitrate were dissolved in deionized water at a molar ratio of Ba, Na, Ru and Al of 3:1:1.8:0.2; then urea in an amount of 1.0 times the total molar amount of Ba, Na, Ru and Al was added and stirred to obtain a mixed solution.
[0055] The mixed solution was heated in an oil bath at 150°C, stirred, and evaporated to dryness. The evaporated material was dried at 160°C for 5 h, then transferred to a muffle furnace and calcined at 1000°C for 12 h to obtain Al-doped Ba 3 NaRu 2 O 9 .
[0056] (2) Preparation of precursor materials A nitrate solution of nickel, cobalt and manganese was prepared according to a molar ratio of Ni:Co:Mn of 0.8:0.1:0.1. A hydroxide precursor of nickel, cobalt and manganese was prepared by a coprecipitation process.
[0057] (3) Coating modification Al-doped Ba 3 NaRu2 O 9 The hydroxide precursors of nickel, cobalt and manganese were mixed evenly in a molar ratio of 2:100, and then heat treated at 300°C for 3 hours. After cooling, precursor I was obtained.
[0058] Precursor I was added to the ethanol solution, dispersed, and then 0.5% of the molar amount of the nickel-cobalt-manganese hydroxide precursor MgCl 2 6H 2 O, stirring (it may also be further ultrasonicated after stirring) to obtain a mixed slurry.
[0059] A 2.0 mol / L ammonia solution was added to the mixed slurry at a rate of 2 mL / min until the pH value of the mixed slurry reached 12, and then the addition of ammonia solution was stopped. The mixture was mechanically stirred for 1 hour and then allowed to stand for 2 hours to obtain precursor II.
[0060] Precursor II was mixed with lithium carbonate in a ratio of the total molar amount of Ni, Co, and Mn to the molar amount of Li of 1:1.05, and then sintered at 1000° C. in an oxygen atmosphere for 12 hours to obtain a coated modified positive electrode material.
[0061] Example 3 (1) Preparation of Al-doped Ba 3 NaRu 2 O 9 Barium nitrate, sodium nitrate, ruthenium nitrate and aluminum nitrate were dissolved in deionized water at a molar ratio of Ba, Na, Ru and Al of 3:1:1.95:0.05; then polyethylene glycol in an amount 1.3 times the total molar amount of Ba, Na, Ru and Al was added and stirred to obtain a mixed solution.
[0062] The mixed solution was heated in an oil bath at 100°C, stirred, and evaporated to dryness. The evaporated material was dried at 120°C for 24 hours, then transferred to a muffle furnace and calcined at 700°C for 20 hours to obtain Al-doped Ba 3 NaRu 2 O 9 .
[0063] (2) Preparation of precursor materials A nitrate solution of nickel, cobalt and manganese was prepared according to a molar ratio of Ni:Co:Mn of 0.7:0.2:0.1. A hydroxide precursor of nickel, cobalt and manganese was prepared by a coprecipitation process.
[0064] (3) Coating modification Al-doped Ba 3 NaRu 2 O 9The hydroxide precursors of nickel, cobalt and manganese were mixed evenly in a molar ratio of 0.5:100, and then heat treated at 200°C for 6 hours. After cooling, the precursor I was obtained.
[0065] Precursor I was added to the ethanol solution, dispersed, and then 1% of the molar amount of the nickel-cobalt-manganese hydroxide precursor MgCl 2 6H 2 O, stirring (it may also be further ultrasonicated after stirring) to obtain a mixed slurry.
[0066] A 2.0 mol / L ammonia solution was added to the mixed slurry at a rate of 2 mL / min until the pH value of the mixed solution reached 10, and then the addition of ammonia solution was stopped. The mixture was mechanically stirred for 1 hour and then allowed to stand for 2 hours to obtain precursor II.
[0067] Precursor II was mixed with lithium carbonate in a ratio of the total molar amount of Ni, Co, and Mn to the molar amount of Li of 1:1.01, and then sintered at 700° C. in an oxygen atmosphere for 20 hours to obtain a coated modified positive electrode material.
[0068] Example 4 (1) Preparation of Al-doped Ba 3 NaRu 2 O 9 Barium nitrate, sodium nitrate, ruthenium nitrate and aluminum nitrate were dissolved in deionized water at a molar ratio of Ba, Na, Ru and Al of 3:1:1.8:0.2; then citric acid in an amount 1.4 times the total molar amount of Ba, Na, Ru and Al was added and stirred to obtain a mixed solution.
[0069] The mixed solution was heated in an oil bath at 120°C, stirred, and evaporated to dryness. The evaporated material was dried at 180°C for 5 h, then transferred to a muffle furnace and calcined at 900°C for 5 h to obtain Al-doped Ba 3 NaRu 2 O 9 .
[0070] (2) Preparation of precursor materials A nitrate solution of nickel, cobalt and manganese was prepared according to a molar ratio of Ni:Co:Mn of 0.9:0.05:0.05. A hydroxide precursor of nickel, cobalt and manganese was prepared by a coprecipitation process.
[0071] (3) Coating modification Al-doped Ba 3 NaRu 2 O 9 , nickel, cobalt and manganese hydroxide precursors were mixed evenly in a molar ratio of 2:100, and then heat treated at 250°C for 4 hours. After cooling, precursor I was obtained.
[0072] Precursor I was added to the ethanol solution, dispersed, and then 2% of the molar amount of the nickel-cobalt-manganese hydroxide precursor MgCl 2 6H 2 O, and stirring (it may also be subjected to further ultrasonic treatment after stirring) to obtain a mixed solution.
[0073] A 2.0 mol / L ammonia solution was added to the mixed solution at a rate of 2 mL / min until the pH value of the mixed solution reached 11, and then the addition of ammonia solution was stopped. The mixture was mechanically stirred for 1 hour and then allowed to stand for 2 hours to obtain precursor II.
[0074] Precursor II was mixed with lithium carbonate in a ratio of the total molar amount of Ni, Co, and Mn to the molar amount of Li of 1:1.1, and then sintered at 1000° C. in an oxygen atmosphere for 16 hours to obtain a coated modified positive electrode material.
[0075] The positive electrode materials obtained in Examples 1 to 4 and Comparative Examples 1 to 4 were respectively assembled into batteries in the following manner: the positive electrode material, conductive graphite, and PVDF were weighed and ground according to a mass ratio of 8:1:1, dissolved in an appropriate amount of N-methylpyrrolidone (NMP), and stirred evenly to form a slurry, and then the slurry was coated on the current collector aluminum foil, dried at 90 ° C in a blast dryer for 12 hours, and punched into a disc electrode with a diameter of 12 mm. The disc electrode was used as the positive electrode and the metal lithium sheet was used as the negative electrode. The lithium ion secondary electrolyte LB-037 (1M LiPF 6 in DEC:EC:EMC=1:1:1 Vol%) as the electrolyte, Celgard2325 as the separator, and assembled into a LIR2032 button cell.
[0076] Test the electrical performance of the battery: in a 25℃ constant temperature box, charge the battery at a constant current of 0.1C to a voltage of 4.3V, then charge it at a constant voltage of 0.01C, and then discharge it at 0.1C to 3V, and repeat this cycle twice; then charge the battery at a constant current of 0.5C to a voltage of 4.3V, then charge it at a constant voltage of 0.5C, and then discharge it at 0.5C to 3V, and record the charge and discharge capacity.
[0077] Test results such as Figure 4 As shown in the figure, the cycle performance of the positive electrode material without coating modification is very poor. Ba doped with MgO or Al 3 NaRu 2 O 9 Although coating and modifying the positive electrode material can improve the cycle performance of the battery, the improvement effect is not good. 3 NaRu 2 O 9The positive electrode material is modified by coating with composite materials, and the cycle performance of the battery is greatly improved. However, MgO and Al-doped Ba 3 NaRu 2 O 9 The positive electrode material is coated and modified with a composite material, and the battery's cycle performance is even better.
[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A coated modified layered oxide positive electrode material, characterized in that: It includes a core and a coating layer, wherein the chemical expression of the core is LiNi x Co y Mn z O2, wherein 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z=1; the material of the coating layer is a composite material of Al-doped Ba3NaRu2O9 and MgO.
2. The coated modified layered oxide positive electrode material according to claim 1, characterized in that: The mass of the material of the coating layer is 0.5-2% of the mass of the core.
3. The coated modified layered oxide positive electrode material according to claim 1 or 2, characterized in that: The molar ratio of Al-doped Ba3NaRu2O9 and MgO in the material of the coating layer is 1:4~4:
1.
4. A method for preparing a coated modified layered oxide positive electrode material, characterized in that: include: Al-doped Ba3NaRu2O9 and the hydroxide precursor of the layered oxide cathode material are uniformly mixed, and then heat-treated at 200-300°C to obtain precursor I; Precursor I is dispersed in an ethanol solution, and then MgCl2·6H2O is added and stirred to obtain a mixed slurry; Adding an ammonia solution to the mixed slurry and stirring until the pH value reaches 10-12, stop adding the ammonia solution; continue stirring for a period of time and then let it stand to obtain a precursor II; After being washed and dried, the precursor II is mixed with a lithium salt and sintered in an oxygen atmosphere to obtain a coated and modified layered oxide positive electrode material.
5. The method for preparing the coated modified layered oxide positive electrode material according to claim 4, characterized in that: Al-doped Ba3NaRu2O9 was prepared by: Dissolve soluble salts of barium, sodium, ruthenium and aluminum in deionized water at a molar ratio of Ba, Na, Ru and Al of 3:1:2-a:a to obtain a mixed salt solution; wherein 0.05≤a≤0.2; A complexing agent solution is added to the mixed salt solution, and the water in the mixed salt solution is evaporated by heating and stirring; the evaporated material is further dried and then calcined to obtain Al-doped Ba3NaRu2O9.
6. The method for preparing the coated modified layered oxide positive electrode material according to claim 5, characterized in that: Also includes at least one of the following technical features (a) to (f): (a) the soluble salts of barium, sodium, ruthenium and aluminum are nitrates; (b) the complexing agent is one of citric acid, polyethylene glycol and urea; (c) the ratio of the molar amount of the complexing agent to the total molar amount of Ba, Na, Ru and Al in the mixed salt solution is 1 to 1.4:1; (d) evaporating the water in the mixed salt solution at 90-150° C. by means of an oil bath; (e) the drying temperature is 100-180° C.; (f) The calcination temperature is 700-1000° C. and the calcination time is 12-20 hours.
7. The method for preparing the coated modified layered oxide positive electrode material according to claim 4, characterized in that: The heat treatment time is 3 to 6 hours.
8. The method for preparing the coated modified layered oxide positive electrode material according to claim 4, characterized in that: The molar ratio of Al-doped Ba3NaRu2O9, hydroxide precursor of layered oxide cathode material, and MgCl2·6H2O is 0.5~2:100:0.5~2; The chemical expression of the hydroxide precursor of the layered oxide positive electrode material is Ni x Co y Mn z (OH)2, where 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z=1.
9. The method for preparing the coated modified layered oxide positive electrode material according to claim 4, characterized in that: The ratio of the total molar amount of Ni, Co, and Mn in the precursor II to the molar amount of Li in the lithium salt is 1:1.01-1.1; the sintering temperature is 700-1000° C.; and the sintering time is 12-20 hours.
10. A lithium ion battery, characterized in that: It comprises the coated and modified layered oxide positive electrode material as described in any one of claims 1 to 3 or the coated and modified layered oxide positive electrode material prepared by the preparation method as described in any one of claims 4 to 9.
Citation Information
Patent Citations
Anode active material for lithium secondary battery, method for fabricating same, and lithium secondary battery using same
CN104904043A
Positive electrode composite material for lithium-ion batteries and preparation method thereof
CN110277548A
Positive plate, manufacturing method thereof and battery
CN113285052A
Modified lithium manganate positive electrode material and preparation method thereof
CN116598456A
Microreactor comprising a porous ceramic material
FR2958287A1